PENGARUH TERAPI MUSIK TERHADAP PENINGKATAN SKALA MOTORIK PADA PENDERITA STROKE ISKEMIK AKUT - Rahmat Syah Essi*, Jumraini Tammasse**, Abdul Muis**, David Gunawan** (NEURONA, 2012)
INTRODUCTION ELEMENTS OF MUSIC HAVE PREVIOUSLY BEEN USED AS PART OF STROKE REHABILITATION BUT THE POTENTIAL THERAPEUTIC ROLE OF DAILY MUSIC THERAPY HAS RECEIVED VERY LITTLE EMPIRICAL ATTENTION LISTENING TO MUSIC IS A COMPLEX PROCESS FOR THE BRAIN WHICH INVOLVES MOTORIC SYSTEM RECENT STUDIES HAVE EXAMINED THE EFFECT OF MUSIC THERAPY IN THE EARLY STAGES OF RECOVERY STROKE WHEN COMBINED WITH STANDARD CARE THE RESULT SHOWS THAT MUSCLE STRENGTH WAS SIGNIFICANTLY GREATER IN THE MUSIC AND STANDARD CARE GROUP THAN IN THE STANDARD CARE ALONE